Gross motor performance in children prenatally exposed to alcohol and living in remote Australia. (20th July 2016) - Lucas, Barbara R; Latimer, Jane; Doney, Robyn; Watkins, Rochelle E; Tsang, Tracey W; Hawkes, Genevieve; Fitzpatrick, James P; Oscar, June; Carter, Maureen; Elliott, Elizabeth J
Abstract : Aim: This study aimed to determine the gross motor (GM) performance of Aboriginal children living in remote Australia. The relationship between GM skills, prenatal alcohol exposure (PAE) and fetal alcohol spectrum disorders (FASD) was explored. Methods: A population‐based observation study was conducted in 2011 to assess motor performance in children living in the Fitzroy Valley, Western Australia, using the Bruininks–Oseretsky Test of Motor Proficiency (BOT‐2). BOT‐2 data were retrospectively analysed using recently developed software enabling separation of fine and GM outcomes. Results: A total of 108 children (98.1% Aboriginal; 53% male, mean age: 8.7 years) were assessed. Half (52.2%) were exposed to at least 'risky' levels of PAE, and 21 (19%) were diagnosed with an FASD. The mean GM composite score of the cohort (47.0 ± 8.4) approached the BOT‐2 normative mean (50.0 ± 10) and was similar between children with and without PAE ( P = 0.27). This mean score, however, was significantly lower in children with FASD than without (mean difference: −5.5 ± 20.6; P = 0.006). Compared with children without FASD, children with FASD had significant impairment in subtests for running speed and agility (mean difference ± standard deviation (SD): −2.4 ± 8.1; P = 0.003) and strength (mean difference ± SD:−2.8 ± 9.9; P = 0.004) and (ii) a higher proportion than expected had overall GM impairment (≤2 SD: 9.5%; ≤1 SD: 23.8%). In groups with PAE, no PAE and no FASD, GM function approached expected population norms. Conclusions: A higher than expected proportion of children with FASD had GM scores that indicated impairment and need for therapy. Evaluation of GM performance should routinely be included in FASD assessment to determine strategies to optimise child development.